PENYULUHAN KEPADA MASYARAKAT TENTANG PENTINGNYA MELAKSANAKAN PENERAPAN PROTOKOL KESEHATAN DI MASA PANDEMI, MENGIKUTI KEGIATAN ORGANISASI KEMASYARAKATAN DAN REKRUTMEN MAHASISWA BARU IKIP BUDI UTOMO - Faizatun Anisa; Yati Yati; Erwin Lapu Ratundima; Dwi Candra Setiawan; Nikmatul Iza (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Potential-Based Community Service (PMBP) is an extracurricular activity that aims to provide services to the community). This is carried out as a form of elaboration in the implementation of the Tri Dharma of Higher Education in which every intellectual candidate is not only sufficient to understand and understand science and technology (IPTEK), but there is a need for a correlation in the level of social life with society in general and more specifically. for people who need the role of students. In the implementation of this Potential-Based Community Service (PMBP), the executor devoted himself to three types of activities, which were carried out in RW 16 Mangliawan, Sawojajar II Malang Regency, East Java Province. The type of activity is participating in community organizations in RW 16 Mangliawan who are affected by the Covid-19 pandemic, providing counseling about the importance of implementing health protocols at Posyandu and Mrs. PKK RW 16 Mangliawan